The Transformation of Tarutung City into a Religious Tourism Destination, 1880–1990 - Syaiful Anwar; Rusydi Fauzan; Lia Melvira (Warisan: Journal of History and Cultural Heritage, 2026)
This study examines the spatial transformation of a region from an agrarian area into a centre of religious significance. The material object of this research is Tarutung City, which, based on its etymological origin, should have been recognised as the “Durian City.” However, over time, Tarutung has become widely recognised as a religious tourism destination. This transformation is closely linked to the activities of German missionaries since the 1860s, who established Tarutung as a central hub of zending activities in the Silindung region. From the period of Indonesian independence to the present, Tarutung has been predominantly identified as a destination for spiritual tourism, while its original association with durian has gradually faded. This study employs the historical method to trace the socio-cultural and physical changes that illustrate the city's transition from an agrarian landscape into a centre of Protestant Christian spirituality. The preliminary assumption suggests that Tarutung was strategically managed within a colonial regional policy aimed at separating Islamic movements in Aceh and Minangkabau. This spatial policy not only persisted but became further consolidated after Indonesia’s independence, positioning Tarutung as a prominent Protestant religious centre that continues to endure to the present day.